Suicidal Ideation and Associated Variables in University of Potosino Altiplano - Rosales Pérez, José Carlos (Consorcio de Universidades Mexicanas A.C., 2014)
This research is aimed at the recognition of conditions, which, according to the cognitive-behavioral theory of suicidal behavior, characterize the manifestation of suicidal behavior from detecting the presence of suicidal ideation in a sample of 89 students from the University of Matehuala, San Luis Potosi. Therefore, the objective was to identify variables associated with the presence of suicidal ideation. Procedure: Application of an instrument consisting of: Section of personally identifiable information; Section of Psychological Constructs; Suicidal Ideation section. Review of reliability and factorial validity of the scales. Recording of variables associated with the presence of suicidal ideation, based on association model identified with the binary logistic regression technique. Results: Three variables associated with the presence of suicidal ideation were recorded; dysfunctional beliefs regarding requirement of success and low frustration tolerance as risk variable. In addition, perception of family support and a history of psychological care as the protection variables. Discussion: defines the variables associated point out that in this sample, recording the presence of suicidal ideation refers to a preparatory condition of suicidal. What they points to the importance of creating programs for detection and care of conditions recognized in the present study, to improve the quality of life of young people and influence in preventing the development of future suicidal behavior.